Constitution Of India And Reservation In Promotions - Tyagi, Prerna (Trinity Law Review, 2021)
Fundamental rights are provided with in Part III of the Constitution of India. According to  Article 16.4, in the interest of any 'backward class' of people not sufficiently represented in the  state's public authorities, the State may reserve appointments or offices. Explaining the nature  of this article, A.C in Mohan Kumar Singhania v. Union of India stated that it is indeed "an  enabling provision" which conferred a discretionary discretion on the State, in favor of any  backwards citizens' class that is not sufficiently represented at the state's service, to provide,  or reserve, appointees or positions. However, in a recent judgment the Supreme Court  explained the reservation in promotion as a non-fundamental right. In this paper, I will provide a quick overview of the constitutional history of reservations in  public job promotions and its current state of affairs.
Keywords: Reservation In Promotions; backward class; enabling provision